POLA KOMUNIKASI KOMUNITAS JARINGAN PENGUSAHA NASIONAL BANDUNG DALAM MEMPERTAHANKAN EKSISTENSINYA - NAJMATUL FAUZIAH (Jurnal Visi Komunikasi, 2022)
Communities are generally formed because there are similarities, visions and missions shared by the people who join in it. Bandung City National Entrepreneur Network. Association of Entrepreneurs whose goal is to establish Japnas, to help the growth of the Indonesian economy, by defending our own products. Japnas Bandung was also established in 2018. This research is how the communication pattern of the Bandung National Entrepreneur Network community in maintaining its existence. This study uses a qualitative approach with a descriptive method. Data collection techniques using interviews, observation and documentation. In this study, the communication pattern used is one-way communication, namely the Japnas website, two-way WhatsApp group media, and multi-way communication occurs during face-to-face meetings such as annual events, Branch Deliberations, Annual Meetings, Break Fasting Together, Halal Bi Halal and Meetings. weekly/monthly. Communication activity in Japnas Bandung City uses descriptive communication, Prescriptive communication (Giving Instructions).